Peculiarities of the volume magnetostriction in La1-xSrxMnO3 in the Curie point region - Koroleva, L. I.; Abramovich, A. I.; Demin, R. V.; Michurin, A. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The parallel l|| and perpendicular l^ magnetostriction with respect to the applied magnetic field and the thermal expansion Dl/l are studied on La1-xSrxMnO3 single crystals with x=0.1, 0.15, and 0.3. For the conducting sample with x=0.3 and the semiconducting sample with x=0.15 the volume magnetostriction (w=l||+2l^) is negative and the |w|(T) curves go through a maximum at the Curie point TC. At T > TC its Dl/l temperature dependence is stronger than the linear one. For the semiconducting sample with x=0.1 w is negative at T < TC and |w|╝0 at T TC. Its Dl/l is linear at T ≥ TC. The behavior of w and Dl/l are explained by a magnetic two-phase state, due to strong s-d exchange.